Evaluation of Refractive Results of LASIK and LASEK in Patients with Myopia and Myopic Astigmatism - Okan Taşkın; Zeynep Özbek (Türk Oftalmoloji Dergisi)
Objectives: To compare the mean visual acuity, spherical equivalent (SE), cylindrical refractive error, and central corneal thickness (CCT) results of LASIK and LASEK in patients with myopia and myopic astigmatism. Materials and Methods: A retrospective review of the patients who underwent LASIK or LASEK for myopia or myopic astigmatism between 2008 and 2011 was performed in the Department of Ophthalmology at Dokuz Eylül University School of Medicine. Preoperative data collected were as follows: Mean SE, mean cylindrical refractive error, best-corrected visual acuity (BCVA), and mean CCT. Postoperative data included mean SE, uncorrected visual acuity (UCVA), mean CCT, and complications at 1, 3, and 6 months, as well as at the last control. The results in the LASIK group were compared to those in the LASEK group. Results: The both (LASIK and LASEK) groups consisted of 60 eyes of 30 patients. All exams and surgeries were performed by one surgeon (ZO). The two groups were similar in terms of age and gender. Mean preoperative SE and BCVA values of the two groups were similar. The mean preoperative cylindrical refractive error values were significantly higher in the LASEK group (p=0.02). The mean preoperative CCT values were significantly lower in the LASEK group (p=0.0). At one month after the surgery, the mean SE and cylindrical refractive error values were not significantly different, but the mean UCVA values were significantly higher in the LASIK group (p=0.015). At six months, the mean SE, cylindrical refractive error, and UCVA values were not significantly different. The mean follow-up period was 13.4 (9-36 months) months. Mean UCVA values at the last exam were higher than the preoperative mean BCVA values in both LASIK and LASEK groups. Conclusion: Both LASIK and LASEK are effective and safe procedures for correction of myopia and myopic astigmatism. The patients with normal corneal thickness and epithelium, normal lid aperture, and low trauma risk are eligible for both procedures. (Turk J Ophthalmol 2014; 44: 332-6)